EXAMINATION OF THE RELATIONSHIP BETWEEN ENGAGEMENT IN SCIENTIFIC ARGUMENTATION AND CONCEPTUAL KNOWLEDGE - BEKİROĞLU, FERAL (SPRINGER, 2012)
Whereas there are some studies presenting the effects of argumentation on science knowledge development, there is still a need for research discovering the interrelationship between knowledge and argumentation. The purpose of this research was to investigate a possible relationship between students' engagement in argumentation and their conceptual knowledge. A case study design was carried out for this research. The participants of the study were tenth graders studying in an urban all-girls school. There were 5 argumentations promoted in different contexts which were embedded through the dynamics chapter, for a 10-week period. Some of the conclusions drawn from the study are as follows: First, students' quantity and quality of arguments improve through time as they get more involved with argumentation. Second, students' knowledge does not improve instantly when they are involved with argumentation activities, that is, knowledge development in an argumentation process takes time. Third, students' prior knowledge affects their participation in argumentation. Last, there are some patterns that indicate the relationship between argumentation and knowledge. However, students' arguments and their knowledge do not develop at the same time.
Keywords: argumentation; conceptual knowledge; physics; SCIENCE-EDUCATION; SCHOOL SCIENCE; STUDENTS; THINKING; GENETICS; CLASSROOMS; DISCOURSE; QUALITY